Pengaruh Kepemilikan Manajerial, Leverage, Finansial Distress, Dan Ukuran Perusahaan - Muhammad Fikri; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; mas Kismanah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This study aims to determine the effect of managerial ownership, leverage, financial distress, and company size on accounting conservatism in transportation sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study are all companies belonging to the transportation sector in from 2017 to 2021. The total population of 25 companies using the purposive sampling method obtained 12 samples of companies that met the criteria, with a total of 60 data observations. This study used panel data regression analysis with the help of the eviews9 program. The results of the study concluded that managerial ownership had a significant negative effect on accounting conservatism with a significance value of 0.6398, leverage had a significant negative effect on accounting conservatism with a significance value of 0.3907, financial distress had a significant effect on conservatism with a significance value of 0.0000 and firm size negative effect on accounting conservatism with a significance value of 0.1420 .